2019
DOI: 10.1093/ibd/izz142
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Microbial Factors Determine the Pattern of Inflammatory Lesions in a Murine Model of Crohn’s Disease–Like Inflammation

Abstract: Here we provide compelling evidence that inflammation in a murine model of Crohn’s disease–like inflammation is characterized by an immune reaction presumably directed at a disease-relevant microflora in a genetically susceptible host with impaired mucosal barrier function and bacterial clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Excess cell death in the intestinal epithelium resulting from dysregulated RIPK1 and RIPK3 signaling has been linked to intestinal inflammation, [61][62][63] and inducing necroptosis by deleting caspase-8 in IECs is sufficient to induce a lethal inflammatory disease in mice along with Paneth cell depletion. 64,65 We found that RIPK1/3 inhibition ameliorated GVHD and restored Paneth cells in allo-HCT recipient Atg16L1 DIEC mice. Based on these results in the animal model, we were remarkably able to design an ex vivo GVHD platform that reproduced the role of ATG16L1 in IECs.…”
Section: Discussionmentioning
confidence: 81%
“…Excess cell death in the intestinal epithelium resulting from dysregulated RIPK1 and RIPK3 signaling has been linked to intestinal inflammation, [61][62][63] and inducing necroptosis by deleting caspase-8 in IECs is sufficient to induce a lethal inflammatory disease in mice along with Paneth cell depletion. 64,65 We found that RIPK1/3 inhibition ameliorated GVHD and restored Paneth cells in allo-HCT recipient Atg16L1 DIEC mice. Based on these results in the animal model, we were remarkably able to design an ex vivo GVHD platform that reproduced the role of ATG16L1 in IECs.…”
Section: Discussionmentioning
confidence: 81%
“…Some of these ileitis models (Samp/YitFc, Caspase‐8 ∆iec, and FADD ∆iec ) exhibit sterile inflammation which can be augmented by the presence of microbes. In models with sterile inflammation, the Paneth cells may undergo necrosis or necroptosis, which are inherently inflammatory (Stolzer et al, 2020). Inflammatory signals may also derive from danger‐associated molecular patterns (DAMPs) generated from defective autophagy and unfolded proteins (unfolded protein response; UPR) in Paneth cells with sub‐lethal distress (Cadwell et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these studies it has been previously shown that mice lacking this central cell death regulator (Casp8 IEC ) in intestinal epithelial cells spontaneously develop intestinal inflammation with histomorphological alterations similar to the classical features of Crohn's disease. Accordingly, Casp8 IEC mice mimic several important characteristics including Paneth cell depletion accompanied by microbial dysbiosis, the culprit of inflammation in the ileum, as well as the immune cell signature (Th1 driven) association with elevated IFN levels (17)(18)(19). Inflammation in these mice is primarily located in the distal part of the small intestine (ileum), and depending on the microbial composition can vary in extent and localization to cause colitis or extensive enteritis (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Casp8 IEC mice mimic several important characteristics including Paneth cell depletion accompanied by microbial dysbiosis, the culprit of inflammation in the ileum, as well as the immune cell signature (Th1 driven) association with elevated IFN levels (17)(18)(19). Inflammation in these mice is primarily located in the distal part of the small intestine (ileum), and depending on the microbial composition can vary in extent and localization to cause colitis or extensive enteritis (17,18). Colonic inflammation is dependent on TNFα signaling, whereas TNFα deficiency is able to ameliorate colonic inflammation, but is not sufficient to prevent Paneth cell loss or enteritis in the small intestine (19,20).…”
Section: Introductionmentioning
confidence: 99%